Design and Development of Combustion Chamber for Portable Food Smoker - FARIS, MUHAMMAD FARIS BIN MOHD HASHIM; SHAARI, MUHAMMAD FARID (Progress in Engineering Application and Technology, 2021)
Smoker’s Burning Chamber is a project that will be applied on the portable smoker device as it will improve the performance of the smoker while it is cooking by preventing direct contact of the food from the fire. The chamber is consist of thermal resistant layer applied on the internal part of the chamber to reduce heat escaping from the chamber. By applying this concept with an appropriate design, this concept will provide better temperature regulation inside the chamber when the burning process occurs. However, in order to chose the right material to be used for the chamber, analysis is done by comparing various type of materials by their characteristic. The components are manufactured with dimensions suitable with the smoker, so the components in the smoker will not obstruct with one another.